Performance quality analysis of brake iron and composite pads for railway rolling composition - E. S. Popov; O. I. Shinsky (Литьë и металлургия)
The requirements for the quality and performance of the brake pads of railway rolling stock made of various materials are analyzed. The advantages of cast iron brake pads produced at foundries are shown. The disadvantages of brake pads made of composite materials based on rubber, asbestos, barite, carbon black and other components are noted. Ways to improve standards, specifications and other documentation for these products are proposed.